Study on the weldability of AA2519 armor grade aluminium alloy - Kosturek, Robert; Śnieżek, Lucjan; Grzelak, Krzysztof; Torzewski, Janusz (Manufacturing Technology Journal, 2022)
This paper describes series of studies concerned with welding of Sc-modified AA2519 at the Military University of Technology. The modification of AA2519 alloy contains a higher concentration of scandium and zirconium and it has been developed in The Institute of Non Ferrous Metals, Light Metals Division in Skawina. The examination involves friction stir welding (FSW) and laser beam welding (LBW) of 5 mm thick AA2519-T62 extrusion. FSW process parameters were: 600 rpm tool rotation speed, 100 mm/min welding velocity, 4.8 mm depth plunge, and MX Triflute tool type. The used LBW parameters were as follows: 3.2 kW laser power, 1.1 m/min welding velocity, 0.2 mm laser beam width, 10° laser beam inclination angle, 10 L/min shielding gas (argon) flow with the laser beam focused on the workpiece surface (f=0). In this work selected results have been presented containing some problems and features typical for investigated joints. Butt joints produced by FSW and LBW have been compared in terms of microstructure (grains), microhardness distribution, joint efficiency, localization of failure, etc. The basic features of weld zones have been discussed together with the distributions of microhardness on the joint's cross-sections. Both welding techniques cause a reduction of microhardness in the weld zone, but the drop from the base material's value (135-140 HV0.1) is far higher in the case of LBW (85-90 HV0.1) than FSW (120 HV0.1). The established values of joint efficiency were 80% (376 MPa) and 66% (314 MPa) for FSW and LBW, respectively. The FSW joints tend to fail in the thermo-mechanically affected zone and LBW in the fusion zone.
Keywords: AA2519; aluminium; laser beam welding; friction stir welding; mechanical properties